A newly developed integrated environment-quality approach for the design of hotel services. (18th October 2006) - Raggi, Andrea; Petti, Luigia
In the perspective of sustainability and industrial ecology, the need to dematerialise economies has become more important. As a consequence, the relative contribution of the service industries to the overall economic output is expected to increase. This entails a growing focus on service-related activities and their ability to meet consumer requirements and society's needs. Among the service industries, one that has become the object of an increased consumer interest is tourism. In this research work, we investigate the main aspects concerning the applicability of existing or newly developed integrated design tools to the above-mentioned service industry, with particular focus on lodging services. In particular, the Quality Function Deployment (QFD) design tool is taken into account and its integration with life cycle-based instruments for environmental assessment is proposed and evaluated with the aim of improving the level of customer satisfaction and the compliance with environmental requirements in lodging services.